4(x-2)=5(x-1)+3x+2

Simple and best practice solution for 4(x-2)=5(x-1)+3x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-2)=5(x-1)+3x+2 equation:


Simplifying
4(x + -2) = 5(x + -1) + 3x + 2

Reorder the terms:
4(-2 + x) = 5(x + -1) + 3x + 2
(-2 * 4 + x * 4) = 5(x + -1) + 3x + 2
(-8 + 4x) = 5(x + -1) + 3x + 2

Reorder the terms:
-8 + 4x = 5(-1 + x) + 3x + 2
-8 + 4x = (-1 * 5 + x * 5) + 3x + 2
-8 + 4x = (-5 + 5x) + 3x + 2

Reorder the terms:
-8 + 4x = -5 + 2 + 5x + 3x

Combine like terms: -5 + 2 = -3
-8 + 4x = -3 + 5x + 3x

Combine like terms: 5x + 3x = 8x
-8 + 4x = -3 + 8x

Solving
-8 + 4x = -3 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-8 + 4x + -8x = -3 + 8x + -8x

Combine like terms: 4x + -8x = -4x
-8 + -4x = -3 + 8x + -8x

Combine like terms: 8x + -8x = 0
-8 + -4x = -3 + 0
-8 + -4x = -3

Add '8' to each side of the equation.
-8 + 8 + -4x = -3 + 8

Combine like terms: -8 + 8 = 0
0 + -4x = -3 + 8
-4x = -3 + 8

Combine like terms: -3 + 8 = 5
-4x = 5

Divide each side by '-4'.
x = -1.25

Simplifying
x = -1.25

See similar equations:

| (7p+8)(2p-3)=9p+5 | | (-362)+421= | | 8+3a=17 | | 4n+11-6n+8m=36 | | -6s=6s-144 | | x-(-19)=-20 | | 3(x-9)-4(3x+1)=x-33 | | 15x-7=8x | | b^4-16a^4=0 | | 3x-6y=-6x+34 | | 4.7x-5.48=11.44 | | (K+2)(6k-7)=0 | | x=ax+1a+bx-2b | | 12-3x+9x=14+6x | | 5x^2+4xy+2y^2=6 | | 3d-274d+10c=120 | | 2x=17x+15 | | 11x+61=Ax+Bx+5A+8B | | 6-2y=10-8y+6y | | x-22x+2y=4 | | 11x+61=Ax+Bx+5A+8A | | (x-2)2x+2y=4 | | (-8)-14= | | 6g-4h=-2g+28 | | 2m-7n-4m+9n= | | 5p+8m=-10p+3 | | 4x-8y=2x+10 | | 8-n(2)=20 | | 81-x^4=0 | | 5N^3+2N^2+15N=0 | | 10+x-(2-3x)=4 | | 1080=26x+95 |

Equations solver categories